2017
DOI: 10.1016/j.ctim.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of hatha yoga amongst persistently depressed individuals enrolled in a trial of yoga for depression

Abstract: Objectives To understand depressed individuals’ experiences in a 10-week hatha yoga program. Design In a randomized controlled trial, participants were assigned to either 10 weeks of hatha yoga classes or a health education control group. This report includes responses from participants in yoga classes. At the start of classes, average depression symptom severity level was moderate. Main outcome measures After 10 weeks of yoga classes, we asked participants (n=50) to provide written responses to open-ended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 19 publications
2
16
0
3
Order By: Relevance
“…However, group yoga classes may not be appropriate for some people with RA, particularly those with restricted mobility and other comorbidities. Additionally, engagement with yoga classes may be particularly challenging for those with depression 26 as well as minority and low income groups due to accessibility and beliefs about the suitability of yoga for arthritis and other health limitations. 27,28 In contrast, individualised yoga therapy is specifically tailored to individual needs and abilities, adapting traditional practices of physical postures, breath control, meditation, visualisation and yogic philosophy to suit each patient.…”
Section: Introductionmentioning
confidence: 99%
“…However, group yoga classes may not be appropriate for some people with RA, particularly those with restricted mobility and other comorbidities. Additionally, engagement with yoga classes may be particularly challenging for those with depression 26 as well as minority and low income groups due to accessibility and beliefs about the suitability of yoga for arthritis and other health limitations. 27,28 In contrast, individualised yoga therapy is specifically tailored to individual needs and abilities, adapting traditional practices of physical postures, breath control, meditation, visualisation and yogic philosophy to suit each patient.…”
Section: Introductionmentioning
confidence: 99%
“…A second, and related possibility, is that people with greater expectancy of success were more likely to engage in informal practice (e.g., noticing one’s breath while in a stressful situation) during the week. Previous analyses of qualitative data suggest that participants in this study did engage in this type of practice (Uebelacker et al, 2017a), and other researchers have also found that people who participate in a yoga class continue to use “tools” learned in yoga, such as breathing practices, gentle stretching, or “centering” even a year after the class (Kinser et al, 2014). However, due to its brevity and integration with day-to-day life, this kind of informal practice may not be reflected in participants’ responses regarding minutes per week of home practice in the current study.…”
Section: Discussionmentioning
confidence: 55%
“…In accordance with our findings, previous yoga studies report that low costs of classes would help to encourage attendance (Atkinson & Permuth‐Levine, ). The participants in the current study considered the instructor to be one of the most important elements to encouraging participation in the mindful yoga programme, and this has been highlighted in earlier yoga studies involving people with depression (Uebelacker et al, ). Our findings suggest that the essential qualities of a mindful yoga instructor include being enthusiastic and knowledgeable, giving clear explanations and demonstrating a caring attitude.…”
Section: Discussionmentioning
confidence: 82%